Coastal Sand Frostweed, Crocanthemum arenicola Synonym: Helianthemum arenicola - Debbie Miller; Mack Thetford; Chris Verlinde; Gabriel Campbell; Ashlynn Smith (EDIS, 2018)
Coastal sand frostweed is found on beach dunes, scrub, and sandhills. It is endemic to the Florida Panhandle, Mississippi, and Alabama coastal counties. After Hurricane Katrina, coastal sand frostweed became the plant with highest frequency on stable dunes on Horn Island, Mississippi (Lucas and Carter 2013). https://edis.ifas.ufl.edu/sg168